A proposed sustainability index for synthesis plans based on input provenance and output fate: application to academic and industrial synthesis plans for vanillin as a case study - Andraos, John (Beilstein Journal of Organic Chemistry, 2020)
This paper describes a sustainability index (SI) as a quantitative measure of “sustainability” applicable to synthesis plans based on the provenance of input materials and energy sources and the fate of output waste products. The index is computed as the root-mean-square average of the following four parameters: mass fraction of valorized inputs (FVI), mass fraction of valorized outputs (FVO), mass fraction of valorized target product (FVP), and input enthalpic energy fraction arising from renewable energy sources (FRE). Valorized input materials originate from renewable, recycled, or reclaimed sources. Valorized output materials are destined for recycling or reclaiming so that they may be used in the same or other chemical processes. Valorized target product refers to that portion of the target product that is actually used for its intended purpose. Renewable energy sources are defined as originating from hydroelectric, wind, solar, geothermal, and biomass sources. The computation of SI is illustrated for 22 synthesis plans of the high commodity flavour ingredient vanillin from biofermentation, chemical synthesis, and solvent extraction processes. In addition, these plans are compared and ranked according to Borda count and poset (partially ordered set) pairwise dominance analyses using the following attributes: process mass intensity (PMI), sacrificial reagent (SR) consumption, input enthalpic energy (IEE) consumption, Rowan solvent greenness index (RSGI), and sustainability index (SI).
Keywords: Borda count; green chemistry; input enthalpic energy; process mass intensity; poset dominance analysis; Rowan solvent greenness index; sacrificial reagent; sustainability; sustainable chemistry

(untitled) - Hogue, C. (Chem. Eng. News, 2019)

(untitled) - Hinderink, A. P.; van der Kooi, H. J.; de Swaan Arons, J. (Green Chem., 1999)

(untitled) - Dewulf, J.; Van Langenhove, H.; Mulder, J.; van den Berg, M. M. D.; van der Kooi, H. J.; de Swaan Arons, J. (Green Chem., 2000)

(untitled) - Lems, S.; van der Kooi, H. J.; de Swaan Arons, J. (Green Chem., 2002)

(untitled) - Cséfalvay, E.; Akien, G. R.; Qi, L.; Horváth, I. T. (Catal. Today, 2015)

(untitled) - Horváth, I. T.; Cséfalvay, E.; Mika, L. T.; Debreczeni, M. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Cséfalvay, E.; Horváth, I. T. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Sikdar, S. K. (AIChE J., 2003)

(untitled) - Sheldon, R. A.; Sanders, J. P. M. (Catal. Today, 2015)

(untitled) - Fadel, C.; Tarabieh, K. (Resources, 2019)

Provenance

(untitled) - McElroy, C. R.; Constantinou, A.; Jones, L. C.; Summerton, L.; Clark, J. H. (Green Chem., 2015)

(untitled) - Jimenez-Gonzalez, C.; Ponder, C. S.; Broxterman, Q. B.; Manley, J. B. (Org. Process Res. Dev., 2011)

(untitled) - Redlich, O.; Kwong, J. N. S. (Chem. Rev., 1949)

(untitled) - Ruiz-Mercado, G. J.; Smith, R. L.; Gonzalez, M. A. (Ind. Eng. Chem. Res., 2012)

Ontario’s System-Wide Electricity Supply Mix: 2017 Data

Archived - 2017 Long-Term Energy Plan: Discussion Guide

(untitled) - Trost, B. M. (Science, 1991)

(untitled) - Slater, C. S.; Savelski, M. (J. Environ. Sci. Health, Part A: Toxic/Hazard. Subst. Environ. Eng., 2007)

(untitled) - Andraos, J. (Green Process. Synth., 2019)

Mémoire de l’Académie Royale. Histoire de l’Académie des Sciences, 1781, 657–665 - de Borda, J. C.

(untitled) - Emerson, P. (Soc. Choice Welfare, 2013)

(untitled) - Levin, J.; Nalebuff, B. (J. Econ. Perspect., 1995)

The Optimal Ranking Method Is the Borda Count - Saari, D. G. (International Institute for Applied Systems Analysis, 1985)

(untitled) - Restrepo, G.; Stadler, P. F. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Li, K.; Frost, J. W. (J. Am. Chem. Soc., 1998)

Eur. Pat. Appl. - Muheim, A.; Müller, B.; Münch, T.; Wetli, M. (Process for the production of vanillin, 1998)

(untitled) - Lesage-Meessen, L.; Delattre, M.; Haon, M.; Thibault, J.-F.; Ceccaldi, B. C.; Brunerie, P.; Asther, M. (J. Biotechnol., 1996)

U.S. Patent - Lesage-Meesen, L.; Delattrea, M.; Haona, M.; Asther, M. (Aspergillus niger which produces vanillic acid from ferulic acid, 2000)

U.S. Patent - Rabenhorst, J.; Hopp, R. (Process for the preparation of vanillin, 1991)

Industrial Chemicals - Faith, W. L.; Keyes, D. B.; Clark, R. L. (Wiley, 1966)

(untitled) - Bjørsvik, H.-R.; Minisci, F. (Org. Process Res. Dev., 1999)

(untitled) - Tomlinson, G. H., 2nd; Hibbert, H. (J. Am. Chem. Soc., 1936)

U.S. Patent - Hibbert, H.; Tomlinson, G. H. (Manufacture of vanillin from waste sulphite pulp liquor, 1937)

U.S. Patent - Craig, D.; Logan, C. D. (Method of producing vanillin and other useful products from lignosulfonic acid compounds, 1962)

(untitled) - Lampman, G. M.; Andrews, J.; Bratz, W.; Hanssen, O.; Kelley, K.; Perry, D.; Ridgeway, A. (J. Chem. Educ., 1977)

U.S. Patent - Sorensen, N. A.; Mehlum, J. (Method of manufacturing vanillin, 1956)

(untitled) - Mayer, E. (Oesterr. Chem.-Ztg., 1949)

(untitled) - Mottern, H. O. (J. Am. Chem. Soc., 1934)

U.S. Patent - Fiecchi, A.; Mario, G.; Cabella, P.; Cicognani, G. (Method of preparing vanillin from eugenol, 1970)

(untitled) - Garner, N.; Siole, A.; Eilks, I. J. (Sci. Educ., 2016)

(untitled) - Huang, W.-B.; Du, C.-Y.; Jiang, J.-A.; Ji, Y.-F. (Res. Chem. Intermed., 2013)

(untitled) - Taber, D. F.; Patel, S.; Hambleton, T. M.; Winkel, E. E. (J. Chem. Educ., 2007)

(untitled) - Sujalmi, S.; Suharso, S.; Supriyanto, R.; Buchari, B. (Indones. J. Chem., 2010)

(untitled) - Sinha, A. K.; Sharma, U. K.; Sharma, N. (Int. J. Food Sci. Nutr., 2008)

(untitled) - Castillo-Ruz, M. C.; Guillermo-Alcocer, C. G.; Bojorquez-Gamboa, R. R.; Rocha-Uribe, J. A. (Tecnol., Cienc., Educ., 2011)

(untitled) - Couteau, D.; Mathaly, P. (Ind. Crops Prod., 1997)

(untitled) - Kaufman, T. S. (J. Braz. Chem. Soc., 2015)

(untitled) - Parfitt, J.; Barthel, M.; Macnaughton, S. (Philos. Trans. R. Soc., B, 2010)

One Third of All Food Wasted! United Nations Regional Information Centre for Western Europe

Global Food Losses and Food Waste – Extent, Causes, and Prevention. Food and Agriculture Organization of the United Nations, Rome, 2011 - Gustavsson, J.; Cederberg, C.; Sonesson, U.; van Otterdijk, R.; Meybeck, A.

Reducing Food Loss and Waste. Working Paper, Installment 2 of Creating a Sustainable Food Future. Washington, DC: World Resources Institute, 2013. - Lipinski, B.; Hanson, C.; Lomax, J.; Kitinoja, L.; Waite, R.; Searchinger, T.

S Department of Agriculture. Food Waste FAQs